Challenges to addressing trafficking into forced labor in Chile: a legal culture perspective - Chan, Carol (Crime, law and social change, 2023)
The meanings of "human trafficking" vary according to political, legal, and sociocultural contexts. This article contributes to understanding the global variation and challenges in enforcing anti-human trafficking laws, by examining how Chilean law enforcement responded to suspected cases of trafficking into forced labor after the Anti-Trafficking Law was enacted in 2011. We present qualitative research on suspected cases of labor trafficking involving Indonesian women in the city of Punta Arenas, including interviews with suspected victims, prosecutors, plaintiff attorneys, anti-trafficking legal advocates, and Indonesian embassy representatives. We argue that four aspects of Chilean legal culture illuminate multiple challenges to identifying and prosecuting cases of labor trafficking in Chile: the perspective that cases of labor disputes and labor trafficking are mutually exclusive; the heterogeneous understandings and definitions of forced labor and human trafficking; the normalization of migrant labor exploitation; and the lack of coordination between relevant institutions and stakeholders. Examining these cases that were investigated between the years 2011 and 2019 allows us to identify the development of a specific legal culture regarding human trafficking into forced labor in Chile.